Synthesis and Biological Evaluation of Depudecin Analogues - Cheng-Sánchez, Iván; Carrillo Fernández, Paloma; García-Ruiz, Cristina; Martínez-Póveda, Beatriz Amparo; Rodríguez-Quesada, Ana María; Medina-Torres, Miguel Ángel; Sarabia-García, Francisco Ramón (My University, 2019)
(-)-Depudecin (1) (Figure 1), isolated from the culture broths of the fungus Alternaria brassicicola,1 and later, from the weed pathogen Nimbya scirpicola,2 has been identified as a selective inhibitor of histone deacetylases (HDAC) with an IC50 in the low M range.3 In contrast to representative HDAC inhibitors, depudecin represents a unique inhibitor of these enzymes by virtue of its molecular structure, featuring the presence of two oxirane rings separated by a trans double bond. Originally discovered as part of a biological screening directed towards the identification of antitumour agents with detransforming activity,4 depudecin was identified as a bioactive metabolite capable of reverting the transformed morphology of tumor cells. This biological activity elicited a great biomedical and biological interest by virtue of its potential as an antitumor agent as well as for further understanding the biological roles of HDACs. Depudecin induced not only morphological changes but also cell cycle arrest and cellular differentiation,5 and also exhibited remarkable anti-angiogenesis activity.6 Prompted by its striking biological properties and enticing structure, we decided to initiate a research program directed towards the synthesis of natural depudecin. Our synthetic plan has recently culminated with linear and convergent total syntheses.7
Keywords: Tumores - Crecimiento; Cáncer - Tratamiento; Depudecin; Natural product; Stereoselective synthesis; Analogues; Antitumoral